The country that they built: The dynamic and complex indigenous economies in North America before 1492 - Ann M. Carlos (Queen's University Centre for Economic History (QUCEH), 2022)
The economic history of the United States is that of Europeans and their institutions. Indigenous nations are absent. This absence is due partly to lack of data but in large measure to a perception that Indigenous communities have contributed little to US growth. This paper argues that this erasure of Indigenous activity overestimates the contributions of European colonists and immigrants. Three case studies explore the economic complexity and social stratification across different nations/regions. Migrants to the Unites States did not come to an empty land but one with settled agriculture, complex production processes and extensive trade relations.
Keywords: J15; N31; N51; N91; 330; Indigenous economic history; North America